2002
DOI: 10.1002/erv.508
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of dissociative experiences to body shape concerns in eating disorders

Abstract: Objective: To examine the relationship of dissociative experiences to body shape concerns in a Spanish sample of eating disorders as compared to a general population. Method: 118 eating disordered outpatients and 64 controls completed the Body Shape Questionnaire (BSQ), the Rosenberg Self-esteem Scale (RSE) and the Dissociative Experiences Scale (DES). Scores were compared within different diagnostic categories. Regression analysis was used to assess the predictive power of the DES and RSES for the BSQ. Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 14 publications
1
24
0
Order By: Relevance
“…An association between body image disturbance and dissociative phenomena has previously been described in patients with bulimic behaviour (Beato, Cano, & Belmonte, 2003;Vanderlinden & Vandereycken, 1997;Vanderlinden, Vandereycken, & Probst, 1995).…”
Section: The Concept Of Body Image Disturbancementioning
confidence: 77%
“…An association between body image disturbance and dissociative phenomena has previously been described in patients with bulimic behaviour (Beato, Cano, & Belmonte, 2003;Vanderlinden & Vandereycken, 1997;Vanderlinden, Vandereycken, & Probst, 1995).…”
Section: The Concept Of Body Image Disturbancementioning
confidence: 77%
“…The DES has been used within previous research to investigate dissociation in relation to eating psychopathology with eating disordered clinical samples (e.g. Beato, Cano, & Belmonte, 2003) as well as student samples (e.g. .…”
Section: )mentioning
confidence: 99%
“…One reason could be the low proportion of patients with bulimia. Persons with this diagnosis have been found to score high on somatoform dissociation in previous studies [16,19,[23][24][25]. This study also included restrictive diagnoses in the clinical group which may have influenced the results.…”
Section: Restraintmentioning
confidence: 99%
“…The degree of somatic dissociation seems to be related to the degree of dissatisfaction about the individual's own body. It may be based on a sensitivity about the body image and seems especially connected with bulimic behavior [24,25]. The relationship has been found so often that it has been suggested that this form of dissociation may distinguish individuals using purging and other compensatory behaviors from those who do not.…”
Section: Introductionmentioning
confidence: 99%